Editorial - Miranda, Diego (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
The institutions Sociedad Colombiana de Ciencias Hortícolas (SCCH), Universidad Pedagógica y Tecnológica de Colombia (UPTC) and Universidad Francisco de Paula Santander (UFPS), editors of the Revista Colombiana de Ciencias Hortícolas (Category B in Publindex - Colciencias), inform our authors and readers that the economic and administrative problems we faced in 2019 have been dealt with, and it is our desire to carry on with our editorial role and continue to strengthen all sections of our journal.